2014
DOI: 10.1074/jbc.m114.604652
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of Multiple Ligand Interactions with the Extracellular Domain of the Calcium-sensing Receptor

Abstract: Background:The calcium-sensing receptor (CaSR) senses alterations in extracellular Ca 2ϩ mainly through its extracellular domain (ECD). Results: Interactions of ligands with the CaSR were characterized using purified ECD and biophysical techniques. Conclusion: Ca 2ϩ and L-Phe bind to both the complex and high mannose forms of the CaSR ECDs and increase binding affinities for each other. Significance: Our findings will provide an essential tool for future structural studies in GPCRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 56 publications
2
23
1
Order By: Relevance
“…The structural requirements for processes such as bias and allosteric modulation of the CaR have been analyzed by recent works [ 95 ]. In addition, a number of papers have highlighted the importance of the potential Ca 2+ binding sites and their relevance for associated diseases [ 8 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Recently, the first high-resolution crystal structure of the ECD of the human CaR bound with Mg 2+ has been proposed [ 102 ].…”
Section: The Extracellular Calcium-sensing Receptor (Car)mentioning
confidence: 99%
“…The structural requirements for processes such as bias and allosteric modulation of the CaR have been analyzed by recent works [ 95 ]. In addition, a number of papers have highlighted the importance of the potential Ca 2+ binding sites and their relevance for associated diseases [ 8 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Recently, the first high-resolution crystal structure of the ECD of the human CaR bound with Mg 2+ has been proposed [ 102 ].…”
Section: The Extracellular Calcium-sensing Receptor (Car)mentioning
confidence: 99%
“…The complex glycosylated and high mannose CaSR ECD (residues 20–612) were purified from HEK293S and its mutant cell line (Zhang et al, 2014c ). Using various spectroscopic methods, it was shown that both form the ECD bound to Ca 2+ with a K d of 3.0–5.0 mM.…”
Section: Identification Of Ca 2+ Binding Sites In mentioning
confidence: 99%
“…The hetero-communication between Ca 2+ and an amino acid functions as a dual switch that globally enhances functional positive homotropic cooperative activation of CaSR in response to Ca 2+ signaling by positively impacting multiple Ca 2+ -binding sites within the ECD (Figure 3 ; Zhang et al, 2014a ). A direct interaction between the CaSR ECD and L-Phe was finally reported using saturation transfer difference NMR approaches with a determined binding affinity of ~10 mM in the absence of Ca 2+ (Zhang et al, 2014c ). The study further demonstrated that L-Phe increases the binding affinity of the CaSR ECD for Ca 2+ .…”
Section: Identification Of Amino Acid Binding Site and Heterotropic Fmentioning
confidence: 99%
“…The ECD contains two sites constantly bound with Ca 2+ and multiple other Ca 2+ -binding sites whose occupancy is dependent on extracellular calcium levels. These varying ECD calcium binding states direct the interaction of the ICD domain with intracellular Ca 2+ [12][13][14].…”
Section: Casr Is Responsible For Cellular Calcium Influxmentioning
confidence: 99%